A Randomized Controlled Trial of Emotion Recognition Training After Traumatic Brain Injury. Issue 3 (May 2015) - Neumann, Dawn; Babbage, Duncan R.; Zupan, Barbra; Willer, Barry
<x xml:space="preserve">Abstract</x> Objective: To examine the effectiveness of 2 affect recognition interventions (Faces and Stories) in people with a traumatic brain injury. Setting: Postacute rehabilitation facilities. Participants: A total of 203 participants with moderate to severe traumatic brain injury were screened; 71 were eligible and randomized to the Faces (n = 24), Stories (n = 23), and Control interventions (n = 24). Participants were an average of 39.8 years of age and 10.3 years postinjury; 74% of participants were male. Design: Randomized controlled trial with immediate, 3-month, and 6-month follow-up posttests. Interventions were 9 hours of computer-based training with a therapist. Measures: Diagnostic Assessment of Nonverbal Accuracy 2-Adult Faces; Emotional Inference From Stories Test; Empathy (Interpersonal Reactivity Index); and Irritability and Aggression (Neuropsychiatric Inventory). Results: The Faces Intervention did significantly better than the Control Intervention on the Diagnostic Assessment of Nonverbal Accuracy 2-Adult Faces (P = .031) posttreatment; no time effect or group interaction was observed. No other significant differences were noted for the Faces Intervention. No significant differences were observed between the Stories and the Control Interventions; however, a significant time effect was found for the Emotional Inference From Stories Test. Conclusion: The Faces Intervention effectively improved facial affect recognition in participants with chronic post–traumatic brain injury, and changes were maintained for 6 months. Future work should focus on generalizing this skill to functional behaviors.